Open Varieties of Capitalism - Becker, U. author. aut Link
X, 222 p. 2 illus.
Keywords: Presenting capitalisms as open, system-like configurations, this book argues four ideal-typical varieties (liberal, statist, corporatist, meso-communitarian) and analyzes the socio-economic performances of advanced capitalisms.